De quelques problèmes épistémologiques dans la théorie du cinéma - Martin Lefebvre (Mise au Point)
In the light of recent debates in film studies over the nature of film theory and the kinds of knowledge it produces, this paper examines some of the epistemological issues currently being raised by film scholars. In particular, it examines the ‘dualistic’ positions that have been developed by Noel Carroll and Malcolm Turvey and seeks to find a ‘third’ way by calling on the philosophy of American pragmatist C. S. Peirce.